Hydroxylapatite implants with or without collagen in the zygomatic arch of rats. Histological study. - Gabrielli, Marisa Aparecida Cabrini; Marcantonio Júnior, Elcio [UNESP]; Góissis, Gilberto; Okamoto, Tetuo [UNESP]; Gabrielli, Mário Francisco Real [UNESP]; Vieira, Eduardo Hochuli [UNESP] (My University, 2001)
The authors studied the behavior of calcium phosphate materials used as inlay implants into bone cavities prepared in the zygomatic arch of rats. Fifty male albino rats were divided into four groups as follows: group I-preparation of bone cavities which did not receive any implant material as controls; group II-implants of Interpore 200; group III-implants of experimental hydroxylapatite; group IV-implants of experimental hydroxylapatite combined with collagen. The animals were sacrificed after 5, 15, 30, 60 and 120 days and the specimens were submitted to histological analysis. Results showed that the experimental hydroxylapatite used in group III presented better osteogenic properties compared to the other materials. All tested materials were biocompatible, although group IV presented a more intense inflammatory response.
Keywords: biomaterial; collagen; hydroxyapatite; animal; bone development; bone prosthesis; comparative study; connective tissue; fibroblast; follow up; giant cell; lymphocyte; macrophage; male; neutrophil; osteoblast; pathology; physiology; rat; Wistar rat; zygoma; Animals; Biocompatible Materials; Bone Substitutes; Collagen; Connective Tissue; Durapatite; Fibroblasts; Follow-Up Studies; Giant Cells; Lymphocytes; Macrophages; Male; Neutrophils; Osteoblasts; Osteogenesis; Rats; Rats, Wistar; Zygoma